2004
DOI: 10.1007/s00122-004-1707-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea

Abstract: Identification of the PCR markers tightly linked to genes that encode important agronomic traits is useful for marker-assisted selection (MAS). The rice Pi5(t) locus confers broad-spectrum resistance to Magnaporthe grisea, the causal agent of rice blast disease. It has been hypothesized that the Pi5(t) locus carries the same gene as that encoded by the Pi3(t) and Pii(t) loci. We developed three PCR-based dominant markers (JJ80-T3, JJ81-T3, and JJ113-T3) from three previously identified BIBAC clones-JJ80, JJ81,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Therefore, one marker set which is useful in a specific cross combination does not always work well in other cross combinations. Although several reports showed that linkage markers can be successfully used to screen for varieties with resistance to rice blast 18,101,107 , almost all markers have never been evaluated as to whether they can be applied to other cross combinations. Information about the markers and their applicability to the combinations of the strains will be valuable for rice breeding using MAS.…”
Section: Limitation For the Universality Of The Markersmentioning
confidence: 99%
“…Therefore, one marker set which is useful in a specific cross combination does not always work well in other cross combinations. Although several reports showed that linkage markers can be successfully used to screen for varieties with resistance to rice blast 18,101,107 , almost all markers have never been evaluated as to whether they can be applied to other cross combinations. Information about the markers and their applicability to the combinations of the strains will be valuable for rice breeding using MAS.…”
Section: Limitation For the Universality Of The Markersmentioning
confidence: 99%
“…Dongjin and Lijiangxintuanheigu (LTH) and two monogenic resistance lines, IRBLb-B carrying Pib and IRBL5-M carrying Pi5 (Tsunematsu et al, 2000;Yi et al, 2004), were obtained from the National Crop Experiment Station, RDA, Suwon, Korea. Dongjin and LTH were used as the respective susceptible controls to the M. oryzae isolates, PO6-6 and race 007.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…AB013448; Table 1). The sequence characterized amplified region (SCAR) markers JJ80-T3-F/R and JJ113-T3-F/R (Table 1; Yi et al, 2004) were used to determine the presence of Pi5 in genomic DNA. Genotyping of OsRAR1 and PCR amplifications were performed as described previously.…”
Section: Dna Extraction and Genotypic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The digested DNA was transferred onto a Hybond N+ nylon membrane (Sambrook et al, 1989), and hybridization was performed using a [α-32 P] dCTP-labeled PAT gene-specific probe prepared using the Rediprime DNA Labeling kit (Amersham Biosciences) in accordance with standard procedures for high-stringency hybridization conditions (Yi et al, 2004). The blot was hybridized in solution containing 0.5 M sodium phosphate (pH 7.2), 1 mM EDTA, 1% (w/v) BSA, and 7% (w/v) SDS for 20 h at 60°C.…”
Section: Plant Regenerationmentioning
confidence: 99%